The effect of deferred tax expense, managerial ownership, and tax planning on profit management - Desi Jelanti (Journal of Economics and Business Letters, 2023)
This study aims to prove empirically the effect of deferred tax expense, managerial ownership, and tax planning on earnings management. This research was conducted in a manufacturing company in the consumer goods industry sector. The type of research used is quantitative with associative method. The type of data used is secondary data in the form of annual financial reports published on the Indonesia Stock Exchange (IDX) for the 2016–2020 period. Samples were collected using purposive sampling method. The number of companies that were used as research samples were 10 companies with a research period of 5 (five) years in order to obtain as many as 50 observational data. The data was processed using the Eviews 9 Statistical Program to test the hypothesis using panel data regression analysis. The results of the F statistical test of deferred tax expense, managerial ownership and tax planning simultaneously have an effect on earnings management. The results of the t-statistical test of deferred tax expense have a positive effect on earnings management and managerial ownership has a negative effect on earnings management, but tax planning has no effect on earnings management.